PENGEMBANGAN E MODUL BERBASIS TEORI BELAJAR BRUNER PADA MATERI JENIS HEWAN VERTEBRATA DAN INVERTEBRATA UNTUK SISWA KELAS III SEKOLAH DASAR - Amniyah Imana; Misbahul Munir (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to develop a Bruner-based IPAS e-module on the topic of vertebrate and invertebrate animals for third-grade elementary students. The research employed a Research and Development (R&D) approach using the 4D model. The needs analysis revealed that 67% of students had difficulty classifying animals, indicating the need for more concrete and interactive learning materials. The e-module was designed by integrating Bruner’s representation stages: enactive, iconic, and symbolic. Validation results indicated that the e-module was categorized as very valid, with scores of 95.54% from media experts, 90.83% from material experts, and 91.82% from learning experts. Additionally, student response testing involving 45 students resulted in a score of 90.97%, categorized as very attractive. These findings suggest that the Bruner-based e-module is valid, practical, and effective in enhancing students’ interest and understanding in IPAS learning at the elementary level.